Strategi Pengembangan Wisata Halal Melalui 3A ( Atraksi, Amenitas dan Aksesibilitas) Studi kasus Hotel Al-Madinah Bangkinang - Adis, Muhammad; Lestari Norhiza, Fitra; Fiatno, Aris (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
By using the 3A method and the Multiple Linear Regression method with fishbone, this study aims to identify indicators that influence halal tourism development strategies, choose the most dominant strategy, and offer suggestions for implementing a Muslim-friendly hotel business. including the ability to bring new perspectives and apply what they have learned in lectures to use in real-world situations, the ability of businesses to account for and contribute to the development of halal tourism strategies, and the potential for universities to benefit students. who conduct additional research in the future. A quantitative descriptive research approach that uses questionnaires, documentation, and techniques to collect observational data. The calculation uses multiple linear regression to provide recommendations for Muslim-friendly hotel businesses and increase the quality and quantity of Al-Madinah hotels by 83.5%.